Pembangunan Spiritual dalam Pelaksanaan Program Tarbiah di Asrama Sekolah-Sekolah Menengah Kebangsaan Agama (SMKA) Pulau Pinang: Spiritual Development in the Implementation of Tarbiah Programme Among Boarding Students at Selected National Religious Secondary Schools (SMKA) in Penang - Mat Jusoh, Mohd Suhardi; Mohd Sharif, Mohd Farid (Afkar: Jurnal Akidah dan Pemikiran Islam, 2018)
This study is to explore the aspects of spiritual development in the implementation of tarbiah programmes at selected National Religious Secondary Schools or SMKA in Penang that consist of SMKA al-Mashoor (L), SMKA al-Mashoor (P), SMKA al-Irsyad and SMKA Nibong Tebal. The main objective of this study is to identify how far the elements of spiritual development are applied in the implementation of the programme, evaluating the involvement of hostel teachers as murabbī and to comprehend the effectiveness of the tarbiah programme towards students’ spiritual development. This study is an exploratory mix-method research with the qualitative data collected through observation and partially-closed interview methods, while the quantitative data is obtained through questionnaires. Overall, the findings from the qualitative part highlighted that only a small number of respondents implemented the elements of spiritual development of mujāhadah al-nafs and al-ihsān. This indirectly revealed that the participation of boarding teachers as murabbī in the student’s spiritual development is at a moderate stage. However, the findings from the quantitative part of the study further confirmed the involvement of boarding teachers as murabbī and manhaj of spiritual development was at a medium high mean (min = 3.78 and 3.18). Similarly, the inferential statistical analysis based on a one-way ANOVA test shows that there is no significant difference (p = 0. 42, p> 0.05) between the length of time the respondent resides in the hostel when explaining the effectiveness of student’s spiritual development through tarbiah programme. Hence, this study concludes that the spiritual development in the implementation of the tarbiah program at SMKA Penang hostel requires a systematic and efficient murabbī organization to realize the objective of spiritual development in the formation of students’ character.